A cross-sectional study among community on knowledge, attitude and practice about blood donation in Udaipur city of Rajasthan, India - Jain, Jyoti; Dixit, Mukul (International Journal Of Community Medicine And Public Health, 2017)
Background: This study has been carried out to find out the knowledge, attitude and practice about blood donation in community of Udaipur city. Methods:This study was conducted in Udaipur city of Rajasthan on the community regarding to know about knowledge, attitude and practice about blood donation. For this sample of 755 respondents were taken during the period of 1st December 2015- 15th January 2016 on the basis of statistical method of sample size determination. Results: Majority of respondents were having awareness and knowledge about blood donation. Practice of donation was found to be more in males are more as compared to females. Females prefer more to donate blood for their relatives and family than others as compared to males. Frequency of donation blood was found to be more in male than female donors. Conclusions:The community has become more aware of the facts about blood donation. More and more people have started donating blood. Thus provision of adequate privacy, awareness communication materials and advertisements to address the fear factor may strengthen the recruitment and retention of voluntary blood donors to donate blood on regular basis to achieve 100% of blood donation.